KOMPETENSI PEMERINTAH DESA DALAM PEMBANGUNAN DESA DI DESA SURYA INDAH KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Nirwana, Cahaya Prima; Tua, Harapan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Goverment’s competence is the important aspect for the rural development of Surya Indah. Training which is done by the Goverment of Surya Indah must be fit to the general training in order to produce the quality human resources. But the budgetary funds for the training is too low. Informations which is gotten from villagers said that the goverment is not good enough for the administration services.This research used theory of Badan Kepegawaian Negara says that competence is defined by indicators of knowledge,skill, and attitude. This research is classified as qualitative descriptive, the technique of collecting data in this research through observation and interview from everyone who are involved as informen.The result of this research shows that the competence of goverment in the Surya Indah village runs well. This is proved from the result of interviews and observation data about aspects knowledge, skills and attitude of govermnet to improve rural development. Factors which influences of the competence of the rural goverment are formal education, training and working experience. Development in Surya Indah are good enough proved from facilities and infrastructures are complete for community life.Key words: Competence, Goverment, Development